2019
DOI: 10.1016/j.jclinepi.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review describes models for recruitment prediction at the design stage of a clinical trial

Abstract: Objective: Patient recruitment in clinical trials is challenging with failure to recruit to time and target sample size common. This may be caused by unanticipated problems or by overestimation of the recruitment rate. This study is a systematic review of statistical models to predict recruitment at the design stage of clinical trials.Study Design and Setting: The Online Resource for Recruitment research in Clinical triAls database was searched to identify articles published between 2008 and 2016. Articles pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 27 publications
0
27
0
1
Order By: Relevance
“…This result has not been reported in the available literature [1-3, 5, 21, 25-29] but seems self-evident as facilities are closed during holidays. Gkioni and colleagues reviewed models for the prediction of recruitment when trials are designed [6]. They described that seasonal variations were considered by only 17% of the predictive models found in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result has not been reported in the available literature [1-3, 5, 21, 25-29] but seems self-evident as facilities are closed during holidays. Gkioni and colleagues reviewed models for the prediction of recruitment when trials are designed [6]. They described that seasonal variations were considered by only 17% of the predictive models found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…This includes careful evaluation of screening and recruitment facilitators as well as barriers. A number of studies have reported factors that impact recruitment at different levels [1][2][3][4][5][6][7], but knowledge about how to best identify the specific target population of asymptomatic participants with early disease stages into studies remains limited. Against this background we assessed the recruitment process and any measures which impacted screening numbers in a study of early, largely asymptomatic stages of age-related macular degeneration (AMD).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review on recruitment models identified 13 articles reporting on different recruitment models and provides a comprehensive exploration on recruitment topics from a statistical perspective [11]. Of note, while in some of the studies a validation of proposed models is reported, systematic empirical investigations and validation studies of proposed recruitment models with large datasets are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, there have been several attempts to define successful strategies for recruitment [5,10] however, the majority have not been formally evaluated [11] or of limited success/lacking implementation [12]. Indeed, recent research confirms that recruitment remains a barrier to successful trial completion, with one paper showing that only just over half (56%) of trials met their recruitment target with or without a study extension [13].…”
Section: Introductionmentioning
confidence: 99%